Biochemical composition, nutritional analysis and antioxidant activity of Buchanania lanzan Spreng fruits - Suryawanshi, Madhuri; Patil, Vilas; Jadhav (Rathod), Varsha (Current Botany, 2021)
Buchanania lanzan Spreng belongs to the family Anacardiaceae. The primary focus of this study was to examine phytochemical, proximate, antioxidant property and GCMS evaluation of unripe and ripen fruit of B. lanzan Spreng. The phytochemical studies showed that alkaloids, phenols, flavones, saponins, coumarins, glycosides and tannins are present in both ripen and unripe fruits. The proximate evaluation confirmed that crude fat (14.5%) and protein (6.37±0.69 g/100g) is high in ripen fruit. In unripe fruit (11.3%) crude fat and protein (4.11%) is less percent. The carotenoid (5.58 ± 0.5 mg/100g) and catalase (0.226±0.074 mg/100g) activity is higher in unripe fruit. The total polyphenol (6.4±0.8 mg/100g) and peroxidase (0.362±0.017 mg/100g) content show greater activity in ripen fruit. In DPPH and FRAP highest activity showed in methanol extract of ripen and unripe fruit than the other solvent. GC-MS evaluation showed many bioactive compounds present in unripe and ripen fruit. It is concluded that nutritional and bioactive ability is high in ripen and unripe fruits of B. lanzan. The fruits of B.lanzan are a good source of nutrition and medicinally important.